2016
DOI: 10.1515/bejeap-2015-0194
|View full text |Cite
|
Sign up to set email alerts
|

Affordable False Teeth: The Effects of Patient Cost Sharing on Denture Utilization and Subjective Chewing Ability

Abstract: We evaluate the impact of patient cost sharing on the use of dentures and subjective chewing ability exploiting a sharp reduction in the coinsurance rate, the percentage of costs born by the user, from 30 % to 10 % at the age of 70 with a regression discontinuity design. Using data from the Japanese Study of Aging and Retirement (JSTAR), we find that the utilization rate of dentures increases from approximately 50 % to 63 % around the threshold, implying that the extensive margin elasticity of denture usage wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 54 publications
2
12
0
Order By: Relevance
“…Finally, we chose not to undertake sex stratified analysis due to the limited sample size and instead performed pooled analyses controlling for sex. Previous research reported that denture utilisation with respect to the reduction of the co-payment in Japan was high for women but close to zero for men (Ando and Takaku 2016). However, our analyses suggested that although women utilised significantly more dental services than men, the effect of co-payment reduction was consistent among both sexes, further supporting the aforementioned analytical choice.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Finally, we chose not to undertake sex stratified analysis due to the limited sample size and instead performed pooled analyses controlling for sex. Previous research reported that denture utilisation with respect to the reduction of the co-payment in Japan was high for women but close to zero for men (Ando and Takaku 2016). However, our analyses suggested that although women utilised significantly more dental services than men, the effect of co-payment reduction was consistent among both sexes, further supporting the aforementioned analytical choice.…”
Section: Discussionsupporting
confidence: 79%
“…Although dental treatments are at high demand among older adults, neither of these studies investigated the utilisation of dental services. Ando and Takaku (2016) used a similar methodology to show the effect of copayment reduction on denture use and subjective chewing ability. However, the data were prior to the implementation of the implementation of current co-payments rates in 2014 and they did not examine the impact of co-payment on dental attendance.…”
Section: Introductionmentioning
confidence: 99%
“…It is necessary to consider indicators that assess social well-being outcomes in addition to oral health. Chewing difficulty is a very subjective indicator 2,15 . It not only depends on the intraoral status (dental caries, periodontal disease, number of teeth, prosthodontics, dentures, and/or dry mouth, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Reports on dental insurance focus on the need for coverage, implementation, disparities in accessibility, and inequalities 7 , 9 14 . Cost reduction is also one of the main foci of dental insurance studies 7 , 8 , 15 , 16 . For example, within the Korean context, after the expansion of dental insurance, the accessibility of dental care improved 10 , 11 , 14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation